New record of a Mesozoic gondwanatherian mammaliaform from Southern Patagonia - Chimento, Nicolás Roberto; Agnolin, Federico; Tsuihiji, Takanobu; Manabe, Makito; Novas, Fernando Emilio (The Science of Nature)
Gondwanatheria is an enigmatic mammaliaform clade distributed in the Cretaceous and Paleogene of South America, Africa, Madagascar, India and Antarctica. The Mesozoic record in South America is restricted to the Latest Cretaceous of Río Negro and Chubut provinces, Argentina and Magallanes Region of southern Chile. The aim of the present contribution is to describe a new specimen of gondwanatherian mammaliaforms from beds belonging to the Maastrichtian Chorrillo Formation, cropping out 30 km SW of El Calafate, Santa Cruz Province, Argentina. It is represented by a single molariform referable to the species Magallanodon baikashkenke with which it shares a unique combination of characters. Analysis of the unique combination of characters exhibited by Magallanodon shed doubts on the monophyly of Ferugliotheriidae and suggest that South American taxa may be closely related to each other. The wide geographical distribution and occurrence of gondwanatherians on geological units of diverse origins suggest that they were capable of facing disparate environmental conditions. Fil: Chimento, Nicolás Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Agnolin, Federico. Fundación de Historia Natural Félix de Azara; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Tsuihiji, Takanobu. National Museum of Nature & Science; Japón Fil: Manabe, Makito. National Museum of Nature & Science; Japón Fil: Novas, Fernando Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina